Biomass for power production and cogeneration - Malico, Isabel (Springer Cham, 2024)
Despite intensive efforts to decarbonise the power sector and the growing contribution of renewables to global electricity generation, fossil fuels, especially coal, continue to dominate as the most commonly used energy sources in this sector. The power industry accounts for a substantial portion of the world total energy supply and remains the largest contributor to CO2 emissions. In 2020, renewable energy sources accounted for 28% of the electricity generation, with only 2% of the electricity produced derived from biofuels. Despite this relatively small share, the role of bioenergy in the power sector holds the potential to contribute to grid stability, a critical factor as the share of intermittent renewables in the energy mix increases. Additionally, co-combustion of biomass in coal power plants offers a cost-effective means of reducing carbon emissions, particularly in regions heavily reliant on coal. Several commercial technologies are available for converting biomass into electricity. While the efficiency of biomass-to-electricity conversion alone is relatively low, combined heat and power plants that utilise waste heat achieve significantly higher overall efficiencies. The choice of technology depends on factors like capacity, efficiency and economic viability. This chapter provides an overview of commonly used conversion technologies for power generation from solid biomass.
Keywords: Electricity; Combined heat and power; Bioenergy; Conversion technologies; Co-combustion